Production of a novel jam spread from honeydew fruit skin by using response surface method - Jamal, Parveen; Yusof, Nurlina; Jaswir, Irwandi (2012)
Honeydew melon (Cucumis melo I) is a favourite fruit for Malaysian. However, due to the fruit skin (unutilized part) a lot of waste is generated, which are not consumed by humans. Studies have shown that 65% - 70% of the honeydew fruit is comprised of fruit pulps, 25% - 30% is the fruit skin and remaining is the melon seeds. Increased production of the honeydew crops influences the amount of unutilized parts (waste) generation that also lead to environmental problems. This demands a solution to use the unutilized part (honeydew skin) for a novel value added product (jam spread) with beneficial qualities. In this study, Faced Cantered Central Composite Design (FCCCD) has been used to optimize the composition of several parameters also, which were the amount of sugar, the amount of pectin and the amount of acid. Sensory evaluation responses were obtained from consumers which proved the acceptability and overall texture of the honeydew skin jam spread.